2017
DOI: 10.1007/s00213-017-4639-0
|View full text |Cite
|
Sign up to set email alerts
|

Cue avoidance training and inhibitory control training for the reduction of alcohol consumption: a comparison of effectiveness and investigation of their mechanisms of action

Abstract: RationaleBoth cue avoidance training (CAT) and inhibitory control training (ICT) reduce alcohol consumption in the laboratory. However, these interventions have never been directly compared and their mechanisms of action are poorly understood.ObjectivesWe compared the effects of both types of training on alcohol consumption and investigated if they led to theoretically predicted changes in alcohol avoidance (CAT) or alcohol inhibition (ICT) associations and changes in evaluation of alcohol cues.MethodsHeavy dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 63 publications
(103 reference statements)
8
62
2
Order By: Relevance
“…In a seminal study, a beer-GNG task which trained heavily drinking students to inhibit responses to "beer" stimuli resulted in significantly reduced weekly alcohol intake relative to students trained towards "beer" stimuli (175). A recent RCT of 120 heavily drinking students found that a single session of either ICT or approach bias modification (ApBM, described below) led to significant reductions in alcohol consumption relative to matched controls (176). Similarly, Kilwein et al (177) found that a single session of ICT (GNG) reduced alcohol consumption and alcohol approach tendencies in a small sample (n = 23) of heavily drinking men (177).…”
Section: Inhibitory Control Training (Ict)mentioning
confidence: 99%
“…In a seminal study, a beer-GNG task which trained heavily drinking students to inhibit responses to "beer" stimuli resulted in significantly reduced weekly alcohol intake relative to students trained towards "beer" stimuli (175). A recent RCT of 120 heavily drinking students found that a single session of either ICT or approach bias modification (ApBM, described below) led to significant reductions in alcohol consumption relative to matched controls (176). Similarly, Kilwein et al (177) found that a single session of ICT (GNG) reduced alcohol consumption and alcohol approach tendencies in a small sample (n = 23) of heavily drinking men (177).…”
Section: Inhibitory Control Training (Ict)mentioning
confidence: 99%
“…We recruited young adult heavy drinkers in accordance with previous laboratory studies of CAT (e.g. Di Lemma and Field 2017;Korucuoglu et al 2014;Wiers et al 2011): heavy drinkers are well-represented in this population, in whom acute alcoholrelated harm is problematic. The study was approved by the University of Liverpool Research Ethics Committee.…”
Section: Participantsmentioning
confidence: 99%
“…Twenty pairs of alcohol-related and matched neutral (control) pictures were used in the computer tasks (Barkby et al 2012;Di Lemma and Field 2017;Field et al 2004). Alcohol pictures depicted alcoholic drinks (e.g.…”
Section: Materials and Tasksmentioning
confidence: 99%
See 2 more Smart Citations